The Effect of Vitamin D and Exercise on Muscle Aging - Jonathan, Agnes Lindrasari; Rizkyah, Ayu; Permata, Ratna Tri; Soesanto, Yenny Boedi; Zerlinda, Visca; Juhanna, Indira Vidiari; Adiatmika, I Putu Gede (Sport and Fitness Journal, 2022)
One of the most essential lifestyle variables that might help you improve with age is physical activity. Physical activity can help you stay in shape and lower your risk of acquiring a range of lifestyle conditions. Muscle mass decreases as people get older. These have an impact on muscle strength, particularly skeletal muscle strength. Vit D is a vitamin that is necessary for muscle strength and contraction. Vitamin D deficiency has been linked to muscle effects such as fatigue and weakness, as well as hormonal and neurological impacts. According to recent research, persons who exercise more had higher vitamin D levels. The major goal of this narrative review was to illustrate the link between vitamin D levels and muscle aging.